الأبعاد الحجاجية في نظرية النظم عند الجرجاني - باي, بن عاشور, مريم الجباري (University of El-oued, 2021)
الملخص: لا ريب في أنَّ الدِّرس العربي القديم يكتسي أهميَّة بالغة، خاصة نظريَّة النَّظم، هذه الأهميَّة لا تظهر إلاَّ من خلال الوقوف على الأثر الذي أحدثته في الدراسات اللِّسانية الحديثة، ولذلك فإنَّ أيَّة محاولة للوقوف على أثر نظريَّة النَّظم عند الجرجاني، لا تمرُّ إلاَّ عبر محاولة أكيدة لفهم كليهما ـــ نظرية النّظْم والنظريات الحديثةـــ ثمَّ العمل على التقاط نقاط الالتقاء بينهما، لذلك جاءت هذه الدِّراسة لتبرز الأبعاد الحجاجيَّة ــــ بوصفها أحد مفرزات الدرس اللِّساني الحديث ــــ لنظرية النَّظْم. Résumé : فرنسية أو انجلزية There is no doubt that the ancient Arabic studies are very important, especially the systems theory. This importance of this theory is shown its effects the in the modern linguistic studies. Therefore, any attempt to Stand on the effect of the systems theory can not be done Only through A real try to understand both the theory of systems and modern theories and then work to capture the points of convergence between them, so this study came to highlight the argumental dimensions as one of the Detachments of the modern linguistic lesson of the systems theory
Keywords: نظرية النَّظْم؛ الدّرس اللساني الحديث؛ الجرجاني؛ الأبعاد الحجاجية؛ التراث اللغوي; systems theory, modern linguistic lesson, al-Jurjani, argumental dimensions, Linguistic heritage.